Получение, структура и свойства гетеронаночастиц SiO2/Au - Матвеевская, Н.А.; Семиноженко, В.П.; Мчедлов-Петросян, Н.О.; Толмачев, А.В.; Шевцов, Н.И. (Видавничий дім "Академперіодика" НАН України, 2007)
The results of preparing and studying the properties of heteronanoparticles on the basis of the monodispersed spherical nanoparticles of silicon dioxide of 40, 120, and 350 nm in diameter and a shell of gold of 1-10 nm in thickness are presented. It is shown that the maximum in absorption spectra (plasmonic resonance) is determined by the ratio of the diameters of a dielectric core (nanoparticle SiO2) and a conductive (Au) shell. It has been established that heteronanoparticles SiO2/Au possess high catalytic activity in the decomposition reaction of peroxide which is determined by the amount of gold on the surface of a silicon core, and the size and structure of the surface of heteronanoparticles.